Factors related to the quality of health services at Rambung Community Health Center Tebing Tinggi City - Purba, Arna Fransisca Millyanti; Harahap, Yuri Warda; Atmadja, Linda Stefanie; Djamin, Djamin; Silalahi, Todung Donald Aposan; Malau, Reghita Claudia; Br Bukit, Rosmeri; Iskandar, Dalmy; Zubaidah, Siti; Pakpahan, Enni Halimatussa'diyah (Buletin Kedokteran & Kesehatan Prima, 2025)
Service activites in an organization that the main activitiy is as service’s provider has a very strategic role. The facility that can support health service’s realization through Community Health Center  (PUSKESMAS). Minister of Health Regulation number 43 of 2019 concerning Puskesmas states that Puskesmas is health service that doing public health means and first level individual health, by prioritizing promotive and preventive in their working areas. This study aims to determinate the factors relating to quality of health’s service in Puskesmas Rambung at Tebing Tinggi City. This type of research is quantitative with a cross-sectional approach. With population of average monthly patitent who come for treatment of 68 samples. Sampling method used purposive sampling.The results showed that the variables that relating to health service’s quality at Puskesmas Rambung Tebing Tinggi City are tangibles (p=0,004), responsiveness (p=0,0001), assurance (p=0,0001), and empathy (p=0,0001). Puskesmas health workers must improving reliability through the attitude of officers towards patients, maintaining the cleanliness of the puskesmas environment so that patients who come for treatment feel comfortable and it is health workers considered to improve their performance so that they will be even better in the future.